2021
DOI: 10.3389/fpls.2021.638520
|View full text |Cite
|
Sign up to set email alerts
|

Target Population of Environments for Wheat Breeding in India: Definition, Prediction and Genetic Gains

Abstract: In this study, we defined the target population of environments (TPE) for wheat breeding in India, the largest wheat producer in South Asia, and estimated the correlated response to the selection and prediction ability of five selection environments (SEs) in Mexico. We also estimated grain yield (GY) gains in each TPE. Our analysis used meteorological, soil, and GY data from the international Elite Spring Wheat Yield Trials (ESWYT) distributed by the International Maize and Wheat Improvement Center (CIMMYT) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 34 publications
5
65
0
Order By: Relevance
“…This scenario seems more reasonable when the crop is exposed to low intensity of drought for long periods ( Ben Haj Salah and Tardieu, 1997 ), but not to a severe stress when this condition can cause damage at the cellular level losing the ability of the plant to fully recover from this stressor ( Prasad et al, 2019 ). Nevertheless, this approach has been widely tested and its conclusions validated in sorghum, maize, mungbean, wheat, chickpea, rice, and pea ( Chenu et al, 2011 , 2013 ; Sadras et al, 2012 ; Chauhan et al, 2013 ; Kholová et al, 2013 ; Chauhan and Rachaputi, 2014 ; Cooper et al, 2014 ; Hammer et al, 2014 ; Harrison et al, 2014 ; Heinemann et al, 2015 , 2019 ; Lobell et al, 2015 ; Seyoum et al, 2017 , 2018 ; Crespo-Herrera et al, 2021 ). Using the same method in maize ( Zea mays L.) in the US Corn Belt, Cooper et al (2014) identified relevant water patterns and characterized their spatial distribution for the region.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario seems more reasonable when the crop is exposed to low intensity of drought for long periods ( Ben Haj Salah and Tardieu, 1997 ), but not to a severe stress when this condition can cause damage at the cellular level losing the ability of the plant to fully recover from this stressor ( Prasad et al, 2019 ). Nevertheless, this approach has been widely tested and its conclusions validated in sorghum, maize, mungbean, wheat, chickpea, rice, and pea ( Chenu et al, 2011 , 2013 ; Sadras et al, 2012 ; Chauhan et al, 2013 ; Kholová et al, 2013 ; Chauhan and Rachaputi, 2014 ; Cooper et al, 2014 ; Hammer et al, 2014 ; Harrison et al, 2014 ; Heinemann et al, 2015 , 2019 ; Lobell et al, 2015 ; Seyoum et al, 2017 , 2018 ; Crespo-Herrera et al, 2021 ). Using the same method in maize ( Zea mays L.) in the US Corn Belt, Cooper et al (2014) identified relevant water patterns and characterized their spatial distribution for the region.…”
Section: Discussionmentioning
confidence: 99%
“…CENEB, near Ciudad Obregon, Mexico, is the key research and breeding site for the CIMMYT Global Wheat Program. Multi-year testing and controlled irrigation to create a simulation of diverse selection environments at CENEB have delivered novel high-yield potential germplasms worldwide [45], and research has shown that the conditions at this site represent major CIMMYT target regions for wheat breeding in the developing world [46][47][48].…”
Section: Estimations Of the Allele Effects At Major And More Recently Identified Vrn Ppd And Eps Genesmentioning
confidence: 99%
“…In plant breeding research, mostly based on the selection of bestevaluated genotypes in a certain experimental network, this approach discriminates which genetic and non-genetic factors affect adaptative responses and yield performance. Thus, a conscious and well-conducted environmental characterization is crucial to bridge the results obtained in some experimental networks and expectations for the target population of environments (TPEs) of the breeding program (e.g., Chenu et al, 2011;Heinemann et al, 2015Heinemann et al, , 2019Crespo-Herrera et al, 2021).…”
Section: Introductionmentioning
confidence: 99%